Analisis Pengaruh PeranMarketing Public Relationsterhadap Peningkatan Citra Lido Lakes Resort and Conference Sukabumi (Jurnal Manajemen dan Organisasi, 2020)
The tourism is a priority sector in Indonesia and reliable source to increase of foreign exchange of the country. Along with the increasing competition of hotel industry especially in Bogor regency, the knowledge about how to make a positive image among society is absolutely important. One of the hotel in the Bogor Regency is Lido Lakes & Resort Conference Sukabumi. The purposes of this study are to identify the characteristics of the consumer and to analyze Marketing Public Relations (MPR) effects towards image enhancement of Lido Lakes Resort & Conference Sukabumi. The method of this research are descriptive analysis and Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach. The result of the study showed that publications, social events, and media identity are the variables which positively affects the hotel image. It is therefore recommended for the company to focus on those three significant variables to enhance the hotel image.